Statistics in Forest Engineering Degree Programs: What Should be Taught and Who Should Teach It - Ayuga-Téllez, Esperanza; González, Concepción; Martín-Fernández, Susana (International Journal of Engineering Pedagogy (iJEP), 2023)
Quality in teaching Applied Statistics in the Degree in Forestry Engineering requires initially asking why to teach Statistics, who should teach it and what should be taught. This paper aims to answer these questions. Natural discussion groups have been used as a method to achieve the objectives. These groups were formed by professors from the UPM and the National University of Santiago del Estero, in Argentina. The results reached the consensus of the experts on the subject: the need for statistics in the training of forestry engineers and that the main contents should be descriptive statistics, sampling techniques, estimation and hypothesis testing and linear models. Finally, another result was that the teaching staff should be Forestry Engineers to show and involve students in real and practical cases that solve engineering problems that facilitate student learning.